Kemiskinan Kultural dan Strategi Bertahan Hidup: Studi Tentang Perilaku Pencurian Buah Sawit oleh Masyarakat Lokal di Perkebunan PT Wilmar - Cindy Aulia; Rholand Muary (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2026)
This study examines the paradox of the growth of Indonesia’s palm oil industry, where the impressive economic expansion of giant corporations such as PT Wilmar contrasts sharply with the declining quality of the living environment of local communities, particularly in South Labuhanbatu Regency. Employing a multi-perspective approach that integrates the theories of structural exclusion, cultural poverty, and James Scott’s moral economy, this study aims to analyze the phenomenon of fresh fruit bunch (FFB) theft, commonly referred to as “palm oil ninjas,” not merely as an act of criminality but as a manifestation of everyday resistance and a form of negotiated redistribution of wealth. Based on secondary data analysis and a comprehensive review of relevant literature, the conversion of customary land into Hak Guna Usaha (HGU) concessions has triggered systemic marginalization, undermined local food sovereignty, and created dependence on vulnerable wage labor. This condition has been exacerbated by the ineffectiveness of Corporate Social Responsibility (CSR) programs and the unequal allocation of Village Funds, resulting in social dysfunction and the intergenerational normalization of cultural poverty. The novelty of this study lies in the reconceptualization of palm oil theft as a form of negotiated redistribution within the context of contemporary agrarian inequality. The findings recommend reformulating CSR programs and developing participatory and inclusive plasma plantation schemes to reconstruct the social contract between corporations and local communities.